2019
DOI: 10.5505/turkhijyen.2019.70370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two-year HIV positivity in a tertiary hospital

Abstract: Objective: Human immunodeficiency virus (HIV) is a virus that can be transmitted interpersonally and may causes Acquired Immunedeficiency Syndrome (AIDS). ELISA method is used in laboratory diagnosis and positive results are confirmed by Western-Blot (WB). The aim of this study was to evaluate the rate of HIV positivity in a two-year period in a tertiary hospital. Methods: 59543 blood samples from the Microbiology Laboratory of Izmir Tepecik Education and Research Hospital were tested by macro ELISA (Architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The study data were evaluated retrospectively, and the fact that transmission routes were not reached from epidemiological data is one of the limitations of this study. In some studies conducted in Turkey, as the distribution by gender are examined, it was found that HIV seropositive patients with rates varying between 75.5% and 84.7% mostly consisted of male patients (6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In our study, 62.9% of HIV seropositive patients were male in majority, as in other studies.…”
Section: E a R L Ymentioning
confidence: 99%
See 1 more Smart Citation
“…The study data were evaluated retrospectively, and the fact that transmission routes were not reached from epidemiological data is one of the limitations of this study. In some studies conducted in Turkey, as the distribution by gender are examined, it was found that HIV seropositive patients with rates varying between 75.5% and 84.7% mostly consisted of male patients (6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In our study, 62.9% of HIV seropositive patients were male in majority, as in other studies.…”
Section: E a R L Ymentioning
confidence: 99%
“…As the studies conducted in Turkey are evaluated without selecting a particular group, HIV seropositivity rate was found to be 0.04% and 0.08%, respectively, in two different studies (8,17) conducted in Izmir. In two different studies (14,18) conducted in Ankara, HIV seropositivity rate was 0.087% and 0.006%, respectively, on the other hand, in a study conducted in Istanbul (19), it was found to be 0.068%.…”
Section: E a R L Ymentioning
confidence: 99%